Moderating Role of seniority and educational level in the relationship between emotional intelligence and leadership. - Ait Said Mohamed, Said; tadjine, Ali (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
This study aimed to explore the relationship between emotional intelligence, leadership, and to test the moderating role of seniority and educational level in the relationship between emotional intelligence and leadership. Applying to a sample of teachers and principals of educational. The Golman model (2000) was used for emotional intelligence, and the Black & Mouton model (1960) for leadership. Applying to a sample of teachers and principals of educational. Relying on theoretical literature from previous theories and studies to building the study model. The study relied on the descriptive research design. The study community is represented in all the teachers and principal of the educational institutions of the Directorate of Education in the state of Tiaret. A stratified random sample of (1000) teachers (46) directors of educational institutions from all three educational stages was selected with a response rate of 91 %. For data analysis and testing hypotheses of the study, were used the AMOS (23) and SPSS (23). The study concluded that there is a statistically significant direct positive impact of the emotional intelligence on leadership. And that the variable of seniority and educational level does not play the role of the moderating variable on the relationship between emotional intelligence and leadership.